The rise of hunger among low-income households: an analysis of the risks of food insecurity between 2004 and 2016 in a population-based study of UK adults - Loopstra, R; Reeves, A; Tarasuk, V (BMJ Publishing Group, 2019)
Background Rising food bank use in the past decade in the UK raises questions about whether food insecurity has increased. Using the 2016 Food and You survey, we describe the magnitude and severity of the problem, examine characteristics associated with severity of food insecurity, and examine how vulnerability has changed among low-income households by comparing 2016 data to the 2004 Low Income Diet and Nutrition Survey. Methods The Food and You survey is a representative survey of adults living in England, Wales, and Northern Ireland (n=3118). Generalised ordered logistic regression models were used to examine how socioeconomic characteristics related to severity of food insecurity. Coarsened exact matching was used to match respondents to respondents in the 2004 survey. Logistic regression models were used to examine if food insecurity rose between survey years. Results 20.7% (95% CI 18.7% to 22.8%) of adults experienced food insecurity in 2016, and 2.72% (95% CI 2.07% to 3.58%) were severely food insecure. Younger age, non-white ethnicity, low education, disability, unemployment, and low income were all associated with food insecurity, but only the latter three characteristics were associated with severe food insecurity. Controlling for socioeconomic variables, the probability of low-income adults being food insecure rose from 27.7% (95% CI 24.8% to 30.6 %) in 2004 to 45.8% (95% CI 41.6% to 49.9%) in 2016. The rise was most pronounced for people with disabilities. Conclusions Food insecurity affects economically deprived groups in the UK, but unemployment, disability and low income are characteristics specifically associated with severe food insecurity. Vulnerability to food insecurity has worsened among low-income adults since 2004, particularly among those with disabilities.